The massacres of the oblivion. Napalpí and Rincon Bomba in the genealogy of the genocide and racism of state in Argentine - Trinchero, Héctor Hugo (2009)
The aim of this article is to draw up a genealogy of certain genocide practices in Argentina and, thus, understand the recurrent massacres of native and non-native populations produced by the Argentinean national State in its neo-colonial formation process. Specifically, it will examine two cases which occurred in the past century, long after General Roca's "final solution" in south Argentina and the extermination campaigns carried out by the Argentinean army in the north, and prior to the genocide of the last military dictatorship. These cases are the massacre of Napalpí, which took place in 1924 in Chaco province, and the "Rincón Bomba" massacre of 1947 in Formosa province. Both massacres of indigenous peoples have recently come under review as part of a necessary exercise for truth and memory.